Educational Reforms and Their Positive Externalities on the Labor Market - Fabio Elsenberger; Michael Jan Kendzia (Institute of Labor Economics (IZA), 2023)
Educational reforms aim to improve education quality and accessibility, creating positive externalities like individual growth and societal benefits. Although the global educational attainment has progressed, disparities still exist. This study applies the four-cell matrix developed by Münich and Psacharopoulos (2018) as analytical framework to classify the benefits of schooling into four different quadrants. It distinguishes between private and social benefits on the x-axis and market and non-market benefits on the y-axis. The survey finds that educational reforms and policies significantly impact society's development and progress, improving economic growth, social mobility, and health outcomes. By and large, the investigated reforms vary by country and education level, with some focusing on primary education and access to education while others focus more on tertiary education. The findings reveal that large differences exist in how far certain reforms were already implemented. Developing nations mainly experience non-market benefits like improved health and disease reduction, while developed countries show positive externalities in market and non-market areas. Reforms targeting tertiary education often translate into more positive externalities in the two private quadrants.
Keywords: I0; J6; O1; N3; 330; educational reforms; market benefits; non-market benefits; private benefits; social benefits